Enemies of All Humankind Fictions of Legitimate Violence - Schillings, Sonja (Re-Mapping the Transnational: A Dartmouth Series in American Studies, 2016)
Hostis humani generis, meaning "enemy of humankind," is the legal basis by which Western societies have defined such criminals as pirates, torturers, or terrorists as beyond the pale of civilization. Sonja Schillings argues that this legal fiction does more than characterize certain persons as inherently hostile: it provides a narrative basis for legitimating violence in the name of the state. The work draws attention to a century-old narrative pattern that not only underlies the legal category of enemies of the state, but more generally informs interpretations of imperial expansion, protest against government-sponsored oppression, and the transformation of institutions as "legitimate" interventions on behalf of civilized society.